2017
DOI: 10.5194/aab-60-105-2017
|View full text |Cite
|
Sign up to set email alerts
|

Protein profile and physicochemical characteristics of meat of lambs fed diets supplemented with rapeseed oil, fish oil, carnosic acid, and different chemical forms of selenium

Abstract: Abstract. The objective of this study was to evaluate the physicochemical characteristics of the longissimus muscle of lambs fed a control diet containing 3 % rapeseed oil (RO) (group I); an experimental diet with 2 % RO and 1 % fish oil (FO) (group II); or experimental diets with coupled addition of 2 % RO, 1 % FO, and 0.1 % carnosic acid (CA) (group III) without/with 0.35 ppm Se as selenized yeast (SeY) (group IV) or selenate (SeVI as sodium selenate, Na 2 SeO 4 ) (group V). The results showed that dietary F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 73 publications
2
16
0
Order By: Relevance
“…This result could be explained by the livestock system since the BG and ODj sheep were reared in the same cradle, same livestock system, and practically same feeding. In comparison with the reported results by Polidori et al [ 21 ] in the meat of Fabrianese sheep breed and Przybylski et al [ 50 ] in the meat of Corriedale lambs, the studied meats had a high protein quality and are rich in essential amino acids. The nature of the breeding system adopted by Moroccan breeders was based mainly on pasture rich in greenery (rich in nitrogenous materials) such as Artemisia herba-alba , Stipa tenacissima, and Atriplex halimus , which can explain this recorded wealth [ 51 – 53 ].…”
Section: Resultssupporting
confidence: 48%
“…This result could be explained by the livestock system since the BG and ODj sheep were reared in the same cradle, same livestock system, and practically same feeding. In comparison with the reported results by Polidori et al [ 21 ] in the meat of Fabrianese sheep breed and Przybylski et al [ 50 ] in the meat of Corriedale lambs, the studied meats had a high protein quality and are rich in essential amino acids. The nature of the breeding system adopted by Moroccan breeders was based mainly on pasture rich in greenery (rich in nitrogenous materials) such as Artemisia herba-alba , Stipa tenacissima, and Atriplex halimus , which can explain this recorded wealth [ 51 – 53 ].…”
Section: Resultssupporting
confidence: 48%
“…Our studies show that short-term dietary supplementation of CA and Se as VI Se or Y Se (rich in Se-Met) can be used to modify the concentration of FA, TCh and tocopherols in the PIF, SCF and muscles of lambs without adversely influencing performance or causing physiological disorders in the liver, blood and brain (Eun et al 2013, Rozbicka-Wieczorek et al 2016b, 2016c, Krajewska-Bienias et al 2017, Przybylski et al 2017, Białek et al 2018. Se-compounds are metabolised to intermediates and then utilised for the biosynthesis of Se-Cys-or Se-Met-containing proteins/enzymes in the tissues of mammals (Collins 2017).…”
Section: Discussionmentioning
confidence: 62%
“…The oxidation of polyunsaturated fatty acids (PUFA), cholesterol and proteins in tissues is one of the most prevalent modifications caused by reactive oxygen and nitrogen species (ROS and RNS) in animal organisms (Saheem et al 2017). Numerous studies have indicated that ruminants' tissues are susceptible to oxidation of lipid unsaturated fatty acids (UFA), sulphur-amino acids in proteins or cholesterol in cell membranes (Krajewska-Bienias et al 2017, Morán et al 2017, Przybylski et al 2017. Dietary antioxidants (like seleno-compounds, polyphenols, carotenoids, lycopene or tocopherols) may prevent or delay some types of oxidative damage in tissues of animals and humans (Choe and Min 2009, El-Ramady et al 2015, Gargiulo et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Fu et al (2014) showed a significant influence of stress on the level of glycolytic enzymes such as: Glucose-6-phosphate isomerase, 6-Phosphofructokinase, Glyceraldehyde-3-phosphate dehydrogenase, Phosphoglycerate mutase, Pyruvate kinase, Lactate dehydrogenase, Creatine kinase. Some studies have shown that nutritional factors can significantly affect the sarcoplasmic protein profile and glycolytic enzyme abundance ( Shibata et al, 2009 ; Przybylski et al, 2017 ; Watanabe et al 2020 ). The study of Watanabe et al (2020) showed that reduction in dietary lysine (from 100% to 90% recommended requirement) upregulated 22 metabolites (among them, inter alia, related to glycolytic transformations) and 24 were downregulated.…”
Section: Resultsmentioning
confidence: 99%